When galectins recognize glycans: From biochemistry to physiology and back again - Di Lella, Santiago (2011)
In the past decade, increasing efforts have been devoted to the study of galectins, a family of evolutionarily conserved glycan-binding proteins with multifunctional properties. Galectins function, either intracellularly or extracellularly, as key biological mediators capable of monitoring changes occurring on the cell surface during fundamental biological processes such as cellular communication, inflammation, development, and differentiation. Their highly conserved structures, exquisite carbohydrate specificity, and ability to modulate a broad spectrum of biological processes have captivated a wide range of scientists from a wide spectrum of disciplines, including biochemistry, biophysics, cell biology, and physiology. However, in spite of enormous efforts to dissect the functions and properties of these glycan-binding proteins, limited information about how structural and biochemical aspects of these proteins can influence biological functions is available. In this review, we aim to integrate structural, biochemical, and functional aspects of this bewildering and ancient family of glycan-binding proteins and discuss their implications in physiologic and pathologic settings. © 2011 American Chemical Society.